The Palaeolithic of the northern Red Sea — new investigations in Tabuk and Al-Jawf provinces, Saudi Arabia - Inglis, Robyn H.; Sinclair, Anthony; Alsharekh, Abdullah; Scott, Christopher; Al Otaibi, Dhaifullah (Proceedings of the Seminar for Arabian Studies, 2019)
The land bridge formed by the Sinai Peninsula is one of the major routes proposed for hominin dispersal out of Africa for both Homo erectus and H. sapiens populations, and its neighbouring regions are, therefore, key to understanding these dispersals. Directly adjacent to the land bridge, the Saudi Arabian northern Red Sea and Gulf of Aqaba coastlines have, until now, been subject to only rapid survey for Palaeolithic archaeology in the 1970s–80s, locating a handful of Palaeolithic artefacts. A twelve-day reconnaissance survey was undertaken by a Saudi-UK team along the northern Red Sea and Gulf of Aqaba coast in February 2018 for Palaeolithic artefacts, the results of which are presented in this paper. Thirty-four locations were surveyed, across a range of landscape settings, the majority yielding Acheulean and prepared-core technology lithic artefacts, traditionally ascribed to Homo erectus and H. sapiens populations in Arabia respectively. These observations, while descriptive and necessarily brief, identify a previously undocumented record of Palaeolithic archaeology in a largely unexplored part of Saudi Arabia. The landscape settings in which artefacts were observed provide a geomorphological framework for locating Palaeolithic material in future surveys to realize the potential of the region to understand hominin dispersals from Africa into Arabia and beyond.